Shared Waters, Shared Futures: Reflections on Climate and Indigenous Knowledge - Gauthier, Maeva; Lugt, Eriel; Bagelman, Jen; Kuptana, C.; Tremblay, Crystal; Wiebe, Sarah Marie (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Spending time on the land and the water to connect and share with one another is central to the grounded lived experiences of many diverse Indigenous communities, yet these activities still tend to be optional or even excluded in traditional research. Grounded in conversation, which uplifts Indigenous oral traditional methods, this article reflects on the power of learning and sharing on the land and water, through arts-based and embodied methods. Using collective coding, the paper reflects specifically on activities led as part of a three-year project, ‘Carving out Climate Testimony’, wherein Inuvialuit youth, Coast Salish Indigenous communities and academics came together to explore the complex lived experiences of climate change. We highlight the pedagogical and personal transformations and benefits of land-based learning and the importance of Indigenous mobilities in fostering climate and cultural awareness and action.